Impact of Interpersonal Communication and Peer Supervision on Teacher Performance in Cengkareng West Jakarta - Alanny, Kanti Mustika; Fuad, Nurhattati; Matin, Matin (Universitas Negeri Malang, 2024)
Abstract: The purpose of this study is to investigate the direct positive influence of interpersonal communication and peer supervision on teacher performance in elementary schools. The study aims to understand how these factors contribute to enhancing teacher effectiveness and overall educational quality. The method used in this research is a structural equation model analysis, which allows for the examination of relationships between multiple variables simultaneously. Data was collected through questionnaires distributed to elementary school teachers, and the results were analyzed using statistical software. The findings indicate that both interpersonal communication and peer supervision have significant positive effects on teacher performance. The path coefficients for the influence of interpersonal communication and peer supervision on teacher performance are 0.4148 and 0.7857, respectively, with p-values less than 0.05, indicating strong statistical significance. Additionally, the study highlights the importance of effective communication skills and structured peer supervision programs in fostering a collaborative and supportive educational environment. These results suggest that educational institutions should prioritize developing these areas to improve teacher performance and student outcomes. In conclusion, enhancing interpersonal communication and peer supervision among teachers can lead to significant improvements in teaching effectiveness. Educational institutions are encouraged to implement training and support programs to strengthen these skills, thereby promoting a higher quality of education.Keywords: interpersonal communication; peer supervision; teacher performance